Quelle résilience des espaces agricoles sous « pression » des changements environnementaux à Ziguinchor (Sénégal) ? - Sécou Omar Diedhiou; Oumar Sy; Christine Margetic (Bulletin de l’Association de Géographes Français)
In Ziguinchor (southern Senegal), agriculture practiced in urban farming areas is threatened by the effects of environmental change and demographic dynamics. However, this agriculture, as a strategic component of food resilience and socio-ecological transition, is attracting growing interest. This article uses observations and quantitative and qualitative surveys to study food resilience and the socio-ecological transition in order to highlight the political issues at stake in the face of environmental crises (pollution, salinity, acidification) in the city of Ziguinchor. The results reveal a weakening, or even degradation, of agricultural and natural spaces, reflecting a vulnerability linked in part to their appropriation by the city, and to the impoverishment of ecological systems. Secondly, specific nourishing, resilient and liveable spaces are endowed with a cultural or worship value that encourages their preservation. Finally, we can speak of an ecologisation of agricultural practices which induce a "rebound" or rather rebounds not really taken in charge by local authorities for the moment.